2017
DOI: 10.1021/acs.nanolett.7b04146
|View full text |Cite
|
Sign up to set email alerts
|

Tunable UV-Emitters through Graphene Plasmonics

Abstract: Control over the spontaneous emission of light through tailored optical environments remains a fundamental paradigm in nanophotonics. The use of highly-confined plasmons in materials such as graphene provides a promising platform to enhance transition rates in the IR-THz by many orders of magnitude. However, such enhancements involve near-field plasmon modes or other kinds of near-field coupling like quenching, and it is challenging to use these highly confined modes to harness light in the far-field due to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…These resonances exhibit stronger confinement and longer lifetimes than their noble metal counterparts, and are readily tuned in an active manner via electrostatic gating [12]. For these reasons, the interaction of plasmonic near fields from highly doped graphene with proximal QEs has been predicted to enable observable vacuum Rabi splittings [13], large Purcell enhancement factors [14,15], and electrical control of quantum states [16]. Unfortunately, even at high doping levels, plasmon energies ω p in graphene nanostructures appear in the infrared or terahertz regimes, well-below the frequencies associated with long-lived electronic excitations in robust quantum light sources.…”
Section: Introductionmentioning
confidence: 99%
“…These resonances exhibit stronger confinement and longer lifetimes than their noble metal counterparts, and are readily tuned in an active manner via electrostatic gating [12]. For these reasons, the interaction of plasmonic near fields from highly doped graphene with proximal QEs has been predicted to enable observable vacuum Rabi splittings [13], large Purcell enhancement factors [14,15], and electrical control of quantum states [16]. Unfortunately, even at high doping levels, plasmon energies ω p in graphene nanostructures appear in the infrared or terahertz regimes, well-below the frequencies associated with long-lived electronic excitations in robust quantum light sources.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of photonic nanostructures have been adopted to trap light on monolayer graphene in the spectral range from visible to infrared, such as plasmonic nanoantennas, plasmonic metamateirals, optical waveguides, and photonic crystals [7][8][9][10][11]. Despite of these research achievements, there is few research about the routes to approaching perfect ultraviolet (UV) absorption in monolayer graphene, which has a variety of promising UV applications on photodetectors, light emitters, Raman microscopy, optical sensing and flame monitoring [12][13][14][15]. A previous effort has been focused on achieving high UV absorption in graphene by using a multilayer structure without any nanostructure patterning [16].…”
Section: Introductionmentioning
confidence: 99%
“…In general, multipolar absorption is inherently small because it ensues from the electromagnetic field spatial variation within the molecule 19 . However, over recent years it has been shown that such "forbidden" transitions can be accessed by the deepsubwavelength scattered field produced by graphene nanostructures [47][48][49][50][51][52][53][54][55] . Note in Figs.…”
Section: Resultsmentioning
confidence: 99%